2015
DOI: 10.1007/978-3-319-15976-8_2
|View full text |Cite
|
Sign up to set email alerts
|

Weighted Decomposition in High-Performance Lattice-Boltzmann Simulations: Are Some Lattice Sites More Equal than Others?

Abstract: Obtaining a good load balance is a significant challenge in scaling up lattice-Boltzmann simulations of realistic sparse problems to the exascale. Here we analyze the effect of weighted decomposition on the performance of the HemeLB lattice-Boltzmann simulation environment, when applied to sparse domains. Prior to domain decomposition, we assign wall and in/outlet sites with increased weights which reflect their increased computational cost. We combine our weighted decomposition with a second optimization, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…In other words, HemeLB provides consistent performance for geometries of varying sparsity. This is an interesting result given that previous performance tests of HemeLB by Groen et al [37] reported a notable difference in peak performance for geometries with varying sparsity. Those reports alluded to the possibility that the optimal tradeoff between computation and communication load-imbalance can vary substantially for different HPC systems.…”
Section: B Strong Scaling Analysissupporting
confidence: 60%
See 3 more Smart Citations
“…In other words, HemeLB provides consistent performance for geometries of varying sparsity. This is an interesting result given that previous performance tests of HemeLB by Groen et al [37] reported a notable difference in peak performance for geometries with varying sparsity. Those reports alluded to the possibility that the optimal tradeoff between computation and communication load-imbalance can vary substantially for different HPC systems.…”
Section: B Strong Scaling Analysissupporting
confidence: 60%
“…They reported, in 2013, near-linear scaling up to 32,768 cores. A performance of 153 billion site updates per second (SUP/s) using 49,152 cores on the ARCHER supercomputer was reported by the same authors elsewhere [37].…”
Section: Hemelb: Parallel Lattice Boltzmann For Complex Geometriesmentioning
confidence: 90%
See 2 more Smart Citations
“…It is a MPI parallelised C++ code with world-class scalability for sparse geometries. It can efficiently model flows in sparse cerebral arteries using up to 32,768 cores [22,23] and utilises a weighted domain decomposition approach to minimize the overhead introduced by compute-intensive boundary and in-/outflow conditions [8]. HemeLB allows users to obtain key flow properties such as velocity, pressure and wall shear at predefined intervals of time, using a property-extraction framework.…”
Section: Hemelbmentioning
confidence: 99%